Analysis of Aflatoxins and Ochratoxin A in Cannabis and Cannabis Products by LC–Fluorescence Detection Using Cleanup with Either Multiantibody Immunoaffinity Columns or an Automated System with In-Line Reusable Immunoaffinity Cartridges. (20th April 2020) - Wilcox, Joyce; Pazdanska, Monika; Milligan, Claire; Chan, Danny; MacDonald, Susan J; Donnelly, Carol
Abstract: Background: Evidence of fungal contamination of cannabis plants during drying has raised concerns of potential mycotoxin contamination of leaves and flowers and subsequent contamination of derived edible cannabis products. Methods are, therefore, needed for routine monitoring of cannabis to ensure consumer safety consistent with long-standing controls for mycotoxins such as aflatoxins and ochratoxin A (OTA) in foodstuffs. Objective: To generate preliminary validation data to demonstrate fitness-for-purpose of methods for aflatoxins and OTA in cannabis and cannabis products. Methods: Extraction of solid matrices with acetonitrile–water (75 + 25) and direct analysis of energy drinks after dilution. Extracts were either passed manually though an immunoaffinity column (IAC) containing antibodies to both aflatoxins and OTA or were analyzed sequentially using an automated system with in-line reusable immunoaffinity cartridges for aflatoxins or OTA. In both cases, analysis was by LC with fluorescence detection. Results: Recoveries were in the range of 76–120% with relative SDs from 0.8 to 6.6% for aflatoxins and OTA spiked into cannabis dried leaves and flowers, hemp tea, oils, capsules, cookies, chocolate brownies, and an energy drink. Conclusions: The methods described in this paper are suitable for the cleanup of sample extracts of cannabis and cannabis products. Highlights: Manual and automated methods with IAC cleanup have been shown to be suitable for routine control of aflatoxins and OTA in cannabis and cannabis products.